MS2/Cardio: Towards a Multi-Service Medical Software for Cardiology - Pinciroli, F.; Combi, C.; Pozzi, G.; Rossi, R. (Methods of Information in Medicine, 1992)
Many clinics are interested to use software packages in daily practice, but lack of integration of such packages seriously limits their scope. In practice this often entails switching between programs and interrupting the run of an individual program. A multi-task approach would not solve this problem as it would not eliminate the need to input the same data many times, as often occurs when using separate packages. The construction of a Multi-Service Medical Software package (MSx2) is described, which was also developed as an example of practical integration of some clinically relevant functions. The package runs on a personal computer in an MS-DOS environment and integrates a time-oriented medical record management unit (TOMRU) for data of ambulatory patients, and a drug information management unit (DIMU) concerning posology, content, effects, and possible interactions. Of the possible database configurations allowed by MSx2, the cardiology patient database (MSx2/C) and hypertensive patient database (MSx2/H) were developed and described here. Clinical information to be included in the configurations was obtained after discussion and consensus of clinical practitioners. MSx2/C was distributed to several hundred clinical centers during computerized courses to train future users. MSx2 can easily transfer patient data to statistical processing packages.
Keywords: Time-Oriented Medical Record; Drug Information Management; Software Integration; Database Structure Configuration; Follow-Up Patient Data Management.